Neostructural Realism’s Explanation on Russia-Ukraine War - Hakim, Amri (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2023)
This article aims to explain why NATO keeps expanse on Ukraine, and why Russia responses it through invasion now. By using qualitative methode, library research, and the neostructural realism theory founded that since the dissolution of Soviet Union, NATO has been no longer appropriate abstracted as an alliance but an unipole security coalition, then the NATO expansion on Ukraine can be seen as the continuity of U.S.’ containment policy to Russia, and adding its coalition partners for unilateral action legitimacy in order to maintain its hegemon position which undermine Russia’s Eurasia great power vision and its crucial national security. Meanwhile the uneven distribution of power elements between U.S. and Russia as the macro international structure constraint Russia invasion but the bipolar world through Russia-China unlimited strategic partnership, and the shifting of U.S. offset strategy to Russia on hypersonic missile as the micro structure encourage Russia to take invasion now.